Pemberdayaan Warung Kecil Melalui Pelatihan Pengelolaan Keuangan dan Pemasaran Digital di Desa Jayamukti - Sintia Pratiwi Nainggolan; Etty Zuliawati Zed; Halima Halima (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this community service is to empower small shop owners in Jayamukti Village by providing training on financial management and digital marketing. This training is expected to enhance the shop owners’ skills in efficient financial management and their ability to utilize digital technology for marketing their products. The training was conducted with a practical approach, involving the delivery of material, case studies, and hands-on simulations. The results of this community service show an improvement in participants’ understanding of managing shop finances and utilizing digital platforms for promotion, which is expected to increase the revenue and sustainability of small shops in the village